The Effect of Micro-Sized Carbon Material Mass Variation from Coconut Shell Leftovers Reinforced with Filter Paper towards Fe Filtration of Mataram Canal Water: Nur Baeity Andriyani, Buky Wahyu Pratama, Irnawati Widya Hastuti, Wipsar Sunu Brams Dwandaru - Nur Baeity Andriyani Nur Baeity Andriyani; Buky Wahyu Pratama Buky Wahyu Pratama; Irnawati Widya Hastuti Irnawati Widya Hastuti; Wipsar Sunu Brams Dwandaru Wipsar Sunu Brams Dwandaru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
The aim of this research is to determine the effect of micro-sized carbon material mass variation from coconut shell leftovers or wastes reinforced with filter paper towards Fe filtration of Mataram canal water. Preparation and synthesis of the micro-sized carbon material is conducted via liquid sonication exfoliation (LSE) method using two main equipments, i.e.: a blender and a self-custom made piezoelectric-based ultrasonication apparatus, and then incorporated into a simple filtration apparatus. UV-Vis spectroscopy characterization is done on the micro-sized carbon material solution, while atomic absorption spectroscopy (AAS) is done on samples of Mataram canal water before and after Fe filtration with mass variation of the micro-sized carbon material. The UV-Vis results show that increasing the mass of the micro-sized carbon material increases the absorbance values at the same wavelength. The AAS results confirm that the greater the mass of the micro-sized carbon material the smaller the Fe content inside the water samples after filtration. The lowest Fe content of 0.016 ppm is obtained for 3 grams of the micro-sized carbon material.